2017
DOI: 10.1016/j.celrep.2017.08.075
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Inactivating KamiCas9 System for the Editing of CNS Disease Genes

Abstract: Neurodegenerative disorders are a major public health problem because of the high frequency of these diseases. Genome editing with the CRISPR/Cas9 system is making it possible to modify the sequence of genes linked to these disorders. We designed the KamiCas9 self-inactivating editing system to achieve transient expression of the Cas9 protein and high editing efficiency. In the first application, the gene responsible for Huntington's disease (HD) was targeted in adult mouse neuronal and glial cells. Mutant hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 59 publications
2
101
0
Order By: Relevance
“…Unlike other approaches, most of which act to control the activity of the CRISPR/Cas system via chemical, 23,24 and biophysical 25,26 modulation of Cas9, our kamikaze CRISPR/Cas system can significantly reduce accumulation of Cas9, and thus off-target cleavage, without dramatically compromising the efficiency of on-target editing. This approach is similar to that used by Merienne and colleagues, 27 who demonstrated that progressively inactivating the nuclease using a Cas9 self-inactivating editing system resulted in a lower frequency of off-target cleavage in human iPSCs-derived neurons in vitro and in mouse brains in vivo . 27 This highlights the potential for a viral-mediated self-destructive CRISPR/Cas systems to be potentially used as a safer tool for in vivo genome editing.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Unlike other approaches, most of which act to control the activity of the CRISPR/Cas system via chemical, 23,24 and biophysical 25,26 modulation of Cas9, our kamikaze CRISPR/Cas system can significantly reduce accumulation of Cas9, and thus off-target cleavage, without dramatically compromising the efficiency of on-target editing. This approach is similar to that used by Merienne and colleagues, 27 who demonstrated that progressively inactivating the nuclease using a Cas9 self-inactivating editing system resulted in a lower frequency of off-target cleavage in human iPSCs-derived neurons in vitro and in mouse brains in vivo . 27 This highlights the potential for a viral-mediated self-destructive CRISPR/Cas systems to be potentially used as a safer tool for in vivo genome editing.…”
Section: Discussionmentioning
confidence: 85%
“…This approach is similar to that used by Merienne and colleagues, 27 who demonstrated that progressively inactivating the nuclease using a Cas9 self-inactivating editing system resulted in a lower frequency of off-target cleavage in human iPSCs-derived neurons in vitro and in mouse brains in vivo . 27 This highlights the potential for a viral-mediated self-destructive CRISPR/Cas systems to be potentially used as a safer tool for in vivo genome editing.…”
Section: Discussionmentioning
confidence: 85%
“…The issue from a safety and regulatory standpoint, of course, is whether the delivery of the Cre enzyme or transgene or the CRISPR agent would be totally effective as well as safe in its own right. The undesired persistence of the Cre or CRISPR transgene could be avoided by having that transgene itself contain DNA sequences that would cause the Cre or CRISPR‐Cas action to inactivate it, as well . Another alternative could be the use of conditional promoters to drive transgene expression.…”
Section: Hurdles That Continue To Slow Down Progress In the Fieldmentioning
confidence: 99%
“…The undesired persistence of the Cre or CRISPR transgene could be avoided by having that transgene itself contain DNA sequences that would cause the Cre or CRISPR-Cas action to inactivate it, as well. 44 Another alternative could be the use of conditional promoters to drive transgene expression. These are promoters that are marginally active in the absence of a co-factor, such as an orally administered drug (e.g., doxycycline) so that the therapy is only "on" while the patient continues taking the oral medication.…”
Section: Clinical Trial Issuesmentioning
confidence: 99%
“…This means that, after a brief flurry of activity by Cas9, production of the DNA-dicing enzyme is inactivated permanently, which dramatically reduces the risk of collateral damage. She notes that several weeks after conventional CRISPR-Cas9 was applied to neural cells derived from people with Huntington's disease, low levels of off-target editing were detected -roughly 2% of modified cells received unwanted edits at a site that is particularly susceptible to off-target editing 5 . By using KamiCas9, her team was able to reduce that effect dramatically -only 0.5% of such modified cells had off-target edits.…”
Section: Gene Editingmentioning
confidence: 99%